Semigroups on time scales and applications to abstract Cauchy problems - Henríquez, Hernán R.; Lizama, Carlos; Mesquita, Jaqueline G. (Topological Methods in Nonlinear Analysis, 2020)
In this paper, we introduce the definition of a $C_0$-semigroup on a time scale, which unifies the continuous, discrete and other cases which lie between them. Also, it extends the classical theory of operator semigroups to the quantum case. We study the relationship between the semigroup and its infinitesimal generator. We apply our theory to study the homogeneous and non homogeneous abstract Cauchy problem in Banach and Fréchet spaces.